FACTORS AFFECTING NON-PERFORMING LOANS IN STATE-OWNED BANKING - Cundo Harimurti; Pandoyo Pandoyo; Mohammad Sofyan (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to analyze the influence of macroeconomic factors projected by inflation and bank-specific factors used, namely Return on Asset, Equity to Asset Ratio, and Bank Size on Non-Performing Loan of State-Owned Banking for the period 2017-2021. This type of research is a causal associative study because it was conducted to determine the effect of Return on Assets, Equity to Asset Ratio, Inflation, and Bank Size on Non-performing State-owned banking Loans for the period 2017-2021. This research data analysis method uses data panel analysis as a data processing tool using EViews version 10. Return on Assets has a significant negative effect on Non-Performing Loans. Equity to Asset Ratio and bank size have a significant positive effect on Non-Performing Loans. Whereas inflation has a positive effect on Non-Performing Loans